The Success of Using Dialogue to Develop Speaking Skill - Mentari Pratami; Erniyanti Nur Fatahhela Dewi (CV. Eureka Murakabi Abadi, 2023)
As University graduates must be able to speak English well. So they are ready when they are faced with the real life and work. So are the graduates of Bina Sarana Informatika University students, they have to gain the language competence especially speaking ability. The aim of the research was to know if the dialogue techniques are effective and appropriate for the university students. The result of the research showed that; 1). Most students got enormous advantages in improving students speaking skill as well as overcoming the speaking difficulties. The improvement covers grammar knowledge, intonation and pronunciation, vocabulary mastery, fluency and naturalness in speaking, and speaking attitude. 2). The students did not feel bored. All students took part actively in the task. It means that students like doing the task. In other words, dialogue technique is one of many good techniques of teaching speaking. 3) During the semester students showed their positive responses to the implementation of the dialogue technique. It can be concluded that the dialogue technique presented in the right way will bring about a good response from the students. In the implementation, the students are happy doing the activity and they are eager to practice speaking. Based on the research result and theoretical review, the writer suggested that dialogue technique is worth to be used for university students especially for conversation subject.